A New Method for the Synthesis of 1,5-Disubstituted 1,2,3-Triazoles via Triazolium Salt Intermediates - Koguchi, Shinichi; Izawa, Kazuki (Synthesis, 2012)
A new transition metal free procedure for the synthesis of 1,5-disubstituted 1,2,3-triazoles, which proceeds via a triazolium salt intermediate is described.
Keywords: triazoles; triazolium salts; azides; alkynes; regioselective